WAVE PROPAGATION ON A FLUME: NUMERICAL SIMULATION - Conde, J. M. P.; Roberto, P. T. S.; Fortes, C. J. E. M. (Revista de Engenharia Térmica, 2015)
This paper presents the numerical simulations done by using the waves2Foam, an OpenFOAM® library, to simulate the propagation of regular waves without breaking in a three-dimensional flume. The numerical code solves the unsteady Navier-Stokes equations and uses a Volume-of-Fluid (VoF) method to identify the free-surface. A regular incident wave with a 1.5s period and 0.1m wave height was considered. This is one of the conditions, from the wide range of wave flume tests conducted at the National Laboratory for Civil Engineering (LNEC), whose objective was to analyze the hydrodynamics of wave transformation and wave breaking for different incident conditions over a variable bathymetry. Comparisons are made between the numerical and the experimental results. These comparisons include time-series of wave-gauges records at several locations along the flume and the corresponding amplitude spectra; significant wave height and average period evolution along the flume; time-series of the velocity components at one section of the flume, measured at the middle of the water column; and hodograph representation of the velocity components, in the middle of the water column, in the xy, xz, and yz planes, along the flume. It was found that the numerical results obtained are close to the experimental data. The observed differences are attributable to numerical inaccuracies as well as the differences between the wave generation method in the numerical and experimental tests.